The Bierwag and Grove Model of the Term Structure of Interest Rates: An Alternative British Test - Buse, A. (The Review of Economics and Statistics, 1968)
Bierwag and Grove [ 1 ] have recently presented an interesting model of the term structure of interest rates which is analytically more appealing than the Meiselman model [5]. In particular, they are able to dispense with the assumption of identical singlevalued expectations and show that individual wealth holders seeking to maximize utility will determine an equilibrium forward rate which is a weighted average of the individual predicted rates. The original Meiselman model is incorporated into this model as a special case. Tests of these new models give good results for the United States using the Durand data [3] but for Britain, using the Grant data [4], the results are generally very poor. This note shows that an alternative set of annual British data, covering yields on government securities for 1933 to 1963, gives results which compare favorably with those for the United States and it is not necessary to conclude, as do Bierwag and Grove, that the expectations mechanism is different in the United Kingdom. The improved results also illustrate the point, elaborated in [2], that the method of yield estimation is the critical factor in tests employing forward interest rates derived from an estimated yield structure. The theoretical model of the term structure developed by Bierwag and Grove shows how a given investment fund is allocated among short and long term bonds given the investor's utility function and the first two moments of his probability distribution of expected interest rates.' The market equilibrium forward rate is then shown to be a weighted average of individual predicted rates. In order to make the model operational, empirical specifications for the formation of interest rate expectations are required. These specifications are of two types: a traditional adaptive expectations function and a Meiselman type adaptive function.2 The relevant equations are specified for each type before the empirical results of the British test are reported.3